PENGARUH LINGKUNGAN KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA PT FORTUNA MULTI FINANCE PONTIANAK - Hendry Mulya Susanto; Deasy Rinayanti Pelealu (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the effect of work environment and work-life balance on employee performance with work motivation as a mediating variable at PT Fortuna Multi Finance Pontianak. This study applies a quantitative approach using a sample of 61 employees selected through total sampling. Data were collected using structured questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that the work environment and work-life balance significantly influence work motivation, while the work environment has a direct and significant impact on employee performance. However, work motivation does not act as a mediating variable in the relationship between work environment and work-life balance on performance. This study highlights that a supportive and conducive work environment is a key factor in determining employee performance in the multifinance industry. Further research is recommended to consider organizational culture and reward systems as potential moderator variables.